Accurate Quantification and Characterization of Adeno-Associated Viral Vectors - Dobnik, David; Kogovšek, Polona; Jakomin, Tjaša; Košir, Nejc; Tušek Žnidarič, Magda; Leskovec, Maja; Kaminsky, Stephen M.; Mostrom, Janet; Lee, Hyunmi; Ravnikar, Maja (Frontiers in Microbiology, 2019)
One of the main challenges in the gene therapy viral vector development is to establish an optimized process for its large scale production. This requires optimization for upstream and downstream processes as well as methods that enable the step-by step analytical characterization of the virus, the results of which inform the iterative refinement of production for yield, purity and potency. The biggest problem here is a plethora of viral vector formulations, many of which interfere with analytical techniques. We took adeno-associated virus (AAV) as an example and showed benefits of combined use of molecular methods and transmission electron microscopy (TEM) for viral vectors’ characterization and quantification. Results of the analyses showed that droplet digital PCR (ddPCR) performs better than quantitative real-time PCR (qPCR), in terms of robustness and assay variance, and this was especially relevant for partially purified (in-process) samples. Moreover, we demonstrate the importance of sample preparation prior to PCR analysis. We evaluated viral structure, presence of aggregates and impurities with TEM analysis and found that these effects impacted the differences in viral titers observed by qPCR and ddPCR and could be altered by sample preparation. These results serve as a guide for the establishment of the analytical methods required to provide measures of identity and purity for AAV viral vectors.